Apigenin inhibits the proliferation of adenoid cystic carcinoma via suppression of glucose transporter-1 - FANG, JIN (D.A. Spandidos, 2015)
Apigenin is a natural phyto-oestrogen flavonoid, which exerts various biological effects, including anti-oxidative, anti-inflammatory and anticancer activities. In addition, apigenin has recently been reported to target hypoxic markers; however, there are currently no studies regarding the association between apigenin and glucose transporter-1 (GLUT-1) in adenoid cystic carcinoma (ACC). The present study investigated whether apigenin inhibits the proliferation of ACC cells or suppresses the expression of GLUT-1 in ACC cells. The results of the present study demonstrated that apigenin inhibits ACC-2 cell growth in a dose- and time-dependent manner. Treatment with apigenin also induced apoptosis and G2/M-phase arrest in a dose- and time-dependent manner. Corresponding with the above results, the expression levels of GLUT-1 were significantly decreased following treatment in a dose- and time-dependent manner. These results suggest that the inhibition of ACC-2 cell growth by apigenin may be due to the decreased expression of GLUT-1.